The Effect of Work Dicipline And Occupational Safety and Health on employee productivity at PT. Citacontrac Jakarta - Aldini Evandra; Sunarti (IECON: International Economics and Business Conference, 2024)
In the globalization era, companies must excel to compete effectively, and human resources play a critical role in organizational success. Human Resource Management (HRM) organizes individuals to drive positive change. This study examines the influence of work discipline and occupational safety and health (OSH) on employee productivity at PT Citacontrac Jakarta. It focuses on three variables: Work Discipline, OSH, and Work Productivity. Using Non-Probability Sampling and Saturated Sampling methods, all 60 employees of PT Citacontrac were included, making it a population study. The analysis employed t-tests to test three hypotheses. The results indicate that Work Discipline significantly and positively impacts Work Productivity (t-value = 2.908 > t-table = 1.295, p < 0.05), leading to the acceptance of H1. Similarly, OSH positively influences Work Productivity (p < 0.05), confirming H2. Finally, the combined effect of Work Discipline and OSH on Work Productivity was significant (t-value = 11.040 > t-table = 1.295, p < 0.05), supporting H3. These findings highlight the importance of enforcing work discipline and ensuring OSH to enhance productivity, emphasizing their collective and individual contributions to organizational success.